2020
DOI: 10.1101/2020.11.16.381806
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Draft Genome Assemblies and Annotations ofAgrypnia vestitaWalker, andHesperophylax magnusBanks Reveal Substantial Repetitive Element Expansion in Tube Case-making Caddisflies (Insecta: Trichoptera)

Abstract: Trichoptera (caddisflies) play an essential role in freshwater ecosystems; for instance, larvae process organic material from the water and are food for a variety of predators. Knowledge on the genomic diversity of caddisflies can facilitate comparative and phylogenetic studies thereby allowing scientists to better understand the evolutionary history of caddisflies. While Trichoptera are the most diverse aquatic insect order, they remain poorly represented in terms of genomic resources. To date, all long-read … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Structurally, this would correspond to defining each repeat as beginning with a single (SX) n E ß-strand [5]. In presenting the new h-fibroin sequences reported here, we have defined the repeating modules as each having two parts: first, a region comprising a variable number (1-6) of (SX) n E motifs, each separated by short (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) stretches of intervening amino acids, and, second, a variable length (8-144 residues) G(glycine) -or G(glycine)-P(proline)-rich region. Schematically, in figure 2, the two parts are represented by different symbols in each block.…”
Section: H-fibroin Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Structurally, this would correspond to defining each repeat as beginning with a single (SX) n E ß-strand [5]. In presenting the new h-fibroin sequences reported here, we have defined the repeating modules as each having two parts: first, a region comprising a variable number (1-6) of (SX) n E motifs, each separated by short (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) stretches of intervening amino acids, and, second, a variable length (8-144 residues) G(glycine) -or G(glycine)-P(proline)-rich region. Schematically, in figure 2, the two parts are represented by different symbols in each block.…”
Section: H-fibroin Structurementioning
confidence: 99%
“…The combination of long-and short-read sequencing approaches resulted in the assembly of two full-length h-fibroin sequences [10,14]. However, the hfibroin could not be assembled in more than 20 species with these sequencing techniques [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the genomes of six trichopteran species, Olsen et al [30] found a 3-fold suborderspecific increase of genome size and hypothesized that genome size variation is correlated with their phylogeny. To test this hypothesis, we first reconstructed phylogenetic relationships by analyzing ~2,000 single-copy BUSCO genes from the 26 study species (Figs.…”
Section: Genome Size Evolution In Trichopteramentioning
confidence: 99%
“…In insects, the known 3 genomic proportion of TEs ranges from 1% in the antarctic midge Belgica antarctica [26] to 65% in the migratory locust Locusta migratoria [27]. Broad-scale analysis of TE abundance in insects suggests that some order-specific signatures are present, however, major shifts in TE abundance are also common at shallow taxonomic levels [28], [29], including in Trichoptera [30]. The movement and proliferation of REs can have deleterious consequences on gene function and genome stability [31], [32], [33], [34], [35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation